A Polarity‐Sensitive Ratiometric Fluorescence Probe for Monitoring Changes in Lipid Droplets and Nucleus during Ferroptosis. (26th May 2021) - Wang, Kang‐Nan; Liu, Liu‐Yi; Mao, Duo; Xu, Shidang; Tan, Cai‐Ping; Cao, Qian; Mao, Zong‐Wan; Liu, Bin
Abstract: Ferroptosis regulates cell death through reactive oxygen species (ROS)‐associated lipid peroxide accumulation, which is expected to affect the structure and polarity of lipid droplets (LDs), but with no clear evidence. Herein, we report the first example of an LD/nucleus dual‐targeted ratiometric fluorescent probe, CQPP, for monitoring polarity changes in the cellular microenvironment. Due to the donor–acceptor structure of CQPP, it offers ratiometric fluorescence emission and fluorescence lifetime signals that reflect polarity variations. Using nucleus imaging as a reference, CQPP was applied to report the increase in LD polarity and the homogenization of polarity between LDs and cytoplasm in the ferroptosis model. This LD/nucleus dual‐targeted fluorescent probe shows the great potential of using fluorescence imaging to study ferroptosis and ferroptosis‐related diseases. Abstract : The first lipid droplet (LD)/nucleus dual‐targeted ratiometric fluorescence probe, CQPP, for monitoring polarity change was developed. CQPP offers ratiometric fluorescence and fluorescence lifetime imaging of LD polarity variations. Using nucleus imaging as a reference, CQPP was applied to report the increase in LD polarity and the homogenization of polarity between LDs and cytoplasm in the ferroptosis model.